2021
DOI: 10.1371/journal.pone.0257175
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound therapy suppresses coronary adventitial inflammatory changes and hyperconstricting responses after coronary stent implantation in pigs in vivo

Abstract: Backgrounds We demonstrated that coronary adventitial inflammation plays important roles in the pathogenesis of drug-eluting stent (DES)-induced coronary hyperconstricting responses in pigs in vivo. However, no therapy is yet available to treat coronary adventitial inflammation. We thus developed the low-intensity pulsed ultrasound (LIPUS) therapy that ameliorates myocardial ischemia by enhancing angiogenesis. Aims We aimed to examine whether our LIPUS therapy suppresses DES-induced coronary hyperconstrictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…21,44,60 In brief, coronary adventitia harbours a wide range of cellular and subcellular components, such as nutrient blood vessels (termed vasa vasorum), perivascular adipose tissue (PVAT), autonomic nervous system, and lymphatic vessels that drain adventitial inflammatory cells. [87][88][89][90][91][92][93][94] We have demonstrated that these adventitial residents have interactions with each other, all of which are involved in coronary hyperconstricting responses after drug-eluting stent (DES) implantation in pigs in vivo (Figure 5). [87][88][89][90][91][92][93] The first observation was that inflammatory changes were potent in the histology of coronary adventitia isolated from the porcine coronary segment with first-generation DES implantation compared with baremetal stent implantation.…”
Section: Roles Of Adventitial Inflammatory Changes In Enhanced Corona...mentioning
confidence: 99%
See 3 more Smart Citations
“…21,44,60 In brief, coronary adventitia harbours a wide range of cellular and subcellular components, such as nutrient blood vessels (termed vasa vasorum), perivascular adipose tissue (PVAT), autonomic nervous system, and lymphatic vessels that drain adventitial inflammatory cells. [87][88][89][90][91][92][93][94] We have demonstrated that these adventitial residents have interactions with each other, all of which are involved in coronary hyperconstricting responses after drug-eluting stent (DES) implantation in pigs in vivo (Figure 5). [87][88][89][90][91][92][93] The first observation was that inflammatory changes were potent in the histology of coronary adventitia isolated from the porcine coronary segment with first-generation DES implantation compared with baremetal stent implantation.…”
Section: Roles Of Adventitial Inflammatory Changes In Enhanced Corona...mentioning
confidence: 99%
“…92 More recent studies underline that impairment of cardiac lymphatic drainage function after DES implantation contributes to sustained adventitial inflammation, medial VSMC hypercontraction and resultant coronary hyperconstriction through activation of Rho-kinase in pigs in vivo. 93,94 We further examined the role of coronary adventitial inflammation in the clinical settings by using a multimodality imaging approach with optical coherence tomography (OCT) and 18 FDG-PET. [98][99][100][101] OCT is capable of visualising coronary adventitial vasa vasorum in pigs and humans and OCT-delineated adventitial vasa vasorum (VV) formation was significantly enhanced at the spastic segments of VSA patients as compared with those of the control subjects (Figure 5).…”
Section: Roles Of Adventitial Inflammatory Changes In Enhanced Corona...mentioning
confidence: 99%
See 2 more Smart Citations
“…LIPUS is already widely used both in various clinical applications and fundamental research (Xin et al, 2016;Xie et al, 2019;Elvey et al, 2020). It has been acknowledged as a non-invasive physical stimulation for therapeutic purposes, delivering acoustic energy to the targeted tissue (de Lucas et al, 2021;Ichijo et al, 2021;Watanabe et al, 2021). Unlike high-intensity ultrasound, LIPUS has drawn attention for its minimal thermal effects (Xin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%